Indoxyl sulfate mediates low handgrip strength and is predictive of high hospitalization rates in patients with end-stage renal disease - Hou, Yi-Chou; Liu, Yueh-Min; Liao, Min-Ter; Zheng, Cai-Mei; Lu, Chien-Lin; Liu, Wen-Chih; Hung, Kuo-Chin; Lin, Shyh-Min; Lu, Kuo-Cheng (Frontiers in Medicine, 2023)
Background and aims Sarcopenia has a higher occurrence rate in patients with chronic kidney disease (CKD) and end-stage renal disease (ESRD) than in the general population. Low handgrip strength—and not sarcopenia per se—is associated with clinical outcomes in patients with CKD, including cardiovascular mortality and hospitalization. The factors contributing to low handgrip strength are still unknown. Accordingly, this study aimed to determine whether uremic toxins influence low handgrip strength in patients with CKD. Materials and methods This cohort study lasted from August 2018 to January 2020. The participants were divided into three groups: the control group [estimated glomerular filtration rate (eGFR) ≥ 60 ml/min], an advanced CKD group (eGFR = 15–60 ml/min), and an ESRD group (under maintenance renal replacement therapy). All participants underwent handgrip strength measurement, dual-energy X-ray absorptiometry, and blood sampling for myokines (irisin, myostatin, and interleukin 6) and indoxyl sulfate. Sarcopenia was defined according to the Asian Working Group for Sarcopenia consensus as low appendicular skeletal muscle index (appendicular skeletal muscle/height2 of < 7.0 kg/m2 in men and < 5.4 kg/m2 in women) and low handgrip strength (< 28 kg in men and < 18 kg in women). Results Among the study participants (control: n = 16; CKD: n = 17; and ESRD: n = 42), the ESRD group had the highest prevalence of low handgrip strength (41.6 vs. 25% and 5.85% in the control and CKD groups, respectively; p < 0.05). The sarcopenia rate was similar among the groups (12.5, 17.6, and 19.5% for the control, CKD, and ESRD groups, respectively; p = 0.864). Low handgrip strength was associated with high hospitalization rates within the total study population during the 600-day follow-up period (p = 0.02). The predictions for cardiovascular mortality and hospitalization were similar among patients with and without sarcopenia (p = 0.190 and p = 0.094). The serum concentrations of indoxyl sulfate were higher in the ESRD group (227.29 ± 92.65 μM vs. 41.97 ± 43.96 μM and 6.54 ± 3.45 μM for the CKD and control groups, respectively; p < 0.05). Myokine concentrations were similar among groups. Indoxyl sulfate was associated with low handgrip strength in univariate and multivariate logistic regression models [univariate odds ratio (OR): 3.485, 95% confidence interval (CI): 1.372–8.852, p = 0.001; multivariate OR: 8.525, 95% CI: 1.807–40.207, p = 0.007]. Conclusion Handgrip strength was lower in the patients with ESRD, and low handgrip strength was predictive of hospitalization in the total study population. Indoxyl sulfate contributed to low handgrip strength and counteracted the benefits of myokines in patients with CKD.